Peran Opinion Leader dalam Komunikasi pada Petani Kelapa Sawit di Desa Surya Indah Kabupaten Pelalawan - Jessica, Josephine; Rosnita, Rosnita; Andriani, Yulia (Journal of Agribusiness and Community Empowerment (JACE), 2022)
In carrying out their farming activities, farmers are strongly influenced by their own characteristics and the information they receive. Information relating to the improvement of oil palm farming is obtained by farmers by communicating with actors who act as sources of information. Subaryadi is the central actor who is often contacted by other farmers to get information related to oil palm farming in Surya Indah Village. This study aims to identify farmers characteristics and analyze the role of opinion leader. This study used a survey method and the sampling used a random sampling technique with a total sample of 33 oil palm farmers. The farmer characteristics were analyzed descriptively, while the role of the SB actor as an opinion leader used a likert scale. The results showed that the characteristics of farmers with the largest percentage were in productive age (54-60 years old on average) with an equivalent high school education level, 4 ha of land area, and high cosmopolitan. Farmers actively participate in extension activities with high accuracy of information channels and complete sources of information. Actor SB carry out his role as opinion leader when implementing the replanting program with a value of 3.33.